Application of the Two-Step Cluster Method in Menu Engineering Analysis at The Alts Hotel Restaurant Palembang, South Sumatra - Lesmana, Andhika Chandra; Setiawan, Agus (Universitas Pendidikan Indonesia, 2024)
ABSTRACTThis research elucidate interm of Hospitality Industry Business especially in Hotel Business, hence restaurants and food businesses as the ones of profit center in hotel often face the challenge of developing menus that are attractive to customers, but also efficient in terms of costs and resources. Effective menu development using the menu engineering method (Menu-Engineering) can increase revenue while achieving customer satisfaction. Therefore, this research uses the menu engineering method as the main basis which aims to identify and analyze existing menus. Furthermore researchers see that selecting a method using Menu-Engineering alone is not enough, especially for determining restaurant management strategy steps to reach the optimal point. Therefore, researchers conducted an in-depth study using the Two-Step Cluster method which is expected to be able to design a menu engineering strategy that can help restaurants increase sales and operational efficiency optimaly. The research object was 5 Stars Hotel in City of Palembang namely “The Alts Hotel”.ABSTRAKPenelitian ini menjelaskan bahwa dalam Industri Perhotelan khususnya Bisnis Hotel, maka Restoran dan bisnis makanan sebagai salah satu “profit center” di hotel seringkali menghadapi tantangan dalam mengembangkan menu yang menarik bagi pelanggan, namun juga efisien dari segi biaya dan sumber daya. Pengembangan menu yang efektif dengan metode rekayasa menu (Menu-Engineering) dapat meningkatkan pendapatan sekaligus mencapai kepuasan pelanggan. Oleh karena itu, penelitian ini menggunakan metode rekayasa menu sebagai landasan utama yang bertujuan untuk mengidentifikasi dan menganalisis menu-menu yang ada. Lebih lanjut Peneliti melihat bahwa pemilihan metode dengan menggunakan Menu-Engineering saja tidak cukup, terutama untuk menentukan langkah-langkah strategi pengelolaan restoran hingga mencapai titik optimal. Oleh karena itu, peneliti melakukan kajian mendalam dengan menggunakan metode Two-Step Cluster yang diharapkan mampu merancang strategi rekayasa menu yang dapat membantu restoran meningkatkan penjualan dan efisiensi operasional secara optimal. Objek penelitiannya adalah Hotel Bintang 5 di Kota Palembang yaitu “The Alts Hotel”.